Analysis the Effect of Macroeconomic Indicators and Specific-Firm Characteristic as Determinant Profitability of Islamic Banks in Asia - Lupita Widyaningrum; Dodik Siswantoro (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2014)
: The purpose of this study is to examine the effect of macroeconomic indicators and specific-firm characteristics on the profitability of Islamic banks in Asia for period 2008-2012. Macroeconomic indicators using variables GDP growth and inflation, while the firm-specific characteristics using variables leverage, capitalization, operating expense, asset quality, number of branches, and firm size. Bank profitability measured by ROA and ROE. Research method using Ordinary Least Squares regression (OLS) to process the data types unbalanced panels and balanced panel. Unbalanced panel using sample of 42 Islamic banks with 188 observations, while on balanced panel using sample of 28 Islamic banks with 140 observations. The result of this research shows that capitalization, firm size, GDP growth, and inflation are determinants affecting ROA with positive and significant influence, while operating expense and leverage are significantly negative determinants that affect ROA. Asset quality and number of branches had no significant influence to ROA. The research also shows that determinant factors that affect ROE with positive and significant influence are captalization, number of branch, GDP growth, and inflation, while operating expense, and asset quality are determinants that affect significantly negative to ROE. Leverage and firm size don’t have significant influence to ROE. These results expected to be useful as a consideration material to improve the performance of Islamic banking, especially in Indonesia in order to compete with Islamic banking in Asia.